2001
DOI: 10.1002/ajim.1120
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of data obtained from migrant farmworkers and their spouses on occupational history†

Abstract: In studies involving farmworkers, when study subjects cannot be interviewed, spouses can provide useful information on occupational histories. However, the information should be used only for more generalized exposure assessments; it is most appropriate for estimating cumulative duration of agricultural work, or recent work, by place or for common crops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Recall bias, though possible, is not likely because associations between kidney disease and occupational exposures were not widely known at the time of the study. Studies have shown reasonable accuracy in proxy respondents' reporting of occupational histories and lower accuracy in the reporting of specific exposures [Lerchen and Samet, ; Colt et al, ; Soll‐Johanning and Hannerz, ]. In our analyses, excluding proxies did not change observed associations.…”
Section: Discussionmentioning
confidence: 39%
“…Recall bias, though possible, is not likely because associations between kidney disease and occupational exposures were not widely known at the time of the study. Studies have shown reasonable accuracy in proxy respondents' reporting of occupational histories and lower accuracy in the reporting of specific exposures [Lerchen and Samet, ; Colt et al, ; Soll‐Johanning and Hannerz, ]. In our analyses, excluding proxies did not change observed associations.…”
Section: Discussionmentioning
confidence: 39%
“…Calendar instruments are currently used in a variety of fields, including life course research ( Axinn et al 1999 ; Caspi et al 1996 ; Reimer 2004 ; Smith and Thomas 2003 ; Van der Vaart 1996 ), epidemiology ( Colt et al 2001 ; Engel et al 2001b ; Hoppin et al 1998 ; Wingo et al 1988 ), family planning studies ( Becker and Diop-Sidibe 2003 ; Becker and Sosa 1992 ; Goldman et al 1989 ; Rosenberg et al 1983 ), health behaviour ( Wiebe and Landis 2000 ), sexual risk taking ( Martyn and Martin 2003 ) and domestic violence ( Yoshihama et al 2005 ). This wide range of topics is also reflected in a great diversity of studied populations.…”
Section: Calendar Instruments: Applications and Rationalementioning
confidence: 99%
“…It provides the first documentation of the lifetime and current pesticide exposure of farmworkers and other Latino immigrants, reflecting efforts that others suggested over a decade ago [Zahm & Blair, 2001; Zahm et al, 1997]. In particular Engel and Colt [Engel et al, 2001; Colt et al, 2001] used a life-time calendar to document the lifetime pesticide exposure of Latino farmworkers. However, although the method they developed appeared to be reliable and valid, the calendar method they used is cumbersome, it was applied to small samples (89 farmworkers and non-farmworkers), and it has not been replicated in other studies.…”
Section: Discussionmentioning
confidence: 99%